Development of a mathematical model of eevaluation of road-and-transport assets as a component of information-and-management system - Slavinska, Оlena; Savenko, Vyacheslav; Kharchenko, Anna; Bubela, Andrey (Eastern-European Journal of Enterprise Technologies, 2017)
The mathematical model of evaluation of road-and-transport assets based on the level of real qualitative state was developed. The study was performed in connection with the lack of evaluation methods that take into account specifics of the assets of the road-and-transport complex. This problem is caused by absence of scientifically substantiated criteria for property evaluation of road assets. As a result of this study, the conceptual model for evaluating the road-and-transport infrastructure assets was developed. Unlike the conventional approach, the constructed conceptual model of the evaluation procedure is based on application of a qualimetric model and a multilevel hierarchical system of indicators. This approach has enabled elucidation of the real physical wear converse to the level of qualitative state of the asset which is the basis for a fair evaluation. The conceptual model of evaluation was laid in the basis of construction of a mathematical model that, in contrast to the conventional approach, takes into account the qualitative state of linearly extensive objects. The disadvantages of application of the developed mathematical model include the necessity of estimation of errors and the level of expert competence. However, the calculations made in testing of this model gives the right to assert fairness of the asset evaluation which is an input parameter to the information-and-management system of the road-and-transport infrastructure. The study results create a favorable environment for making managerial decisions on the assets as the objects of management in the road-and-transport complex and can be used by enterprises and organizations of the complex